Conocimiento en salud oral, ets y cavidad oral en trabajadoras sexuales de tres establecimientos de Cúcuta (2021)
The level of knowledge in oral health of the respondents was bad in 48.2% followed by regular 27%, the level of knowledge in STDs and manifestations in the oral cavity was regular in a high percentage, oral health affects the quality of life in several aspects.